Nuklearno medicinske preiskave v nevrologiji - Hrastnik, Franc (Obzornik zdravstvene nege, 1978)
Cerebral scintigraphy is considered to be a timesaving and safe method used in the detection of the brain affecting diseases. The author present the kinetics of radiopharmaceuticals introduced into the brain as well as the technique and processing of sequential scans using gamma camera. Besides the evaluation of topographic limitation, form, size, blood supply, dynamics of uptake and disttribution of radioisotopes, they render possible a considerably reliable determination of the nature of the pathologic processes.